Effects of prior warm-up regime on severe-intensity cycling performance - Burnley, M.; Doust, J. H.; Jones, A. M. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The purpose of the present study was to determine the effect of three different warm-up regimes on cycling work output during a 7-min performance trial.